Emerging issues on reclaimed land in Malaysia: alienation for freehold or leasehold? - Sufian, Azlinor; Mustafa, Maizatun (2010)
Due to rapid development and land scarcity in the urban areas in Malaysia, the state government has to reclaim the land at the coastal areas in order to meet the need for physical space for commercial activities, housing, public facilities and etc. There are many issues derived from land reclamation; among others environmental degradation, instability of reclaimed land, long term excessive settlement and land reclamation disputes between the states. However in this paper the focus is on the meaning of reclaimed land, powers of the state authority in matters pertaining to reclaimed land, process of alienation of reclaimed land and issuance of title of reclaimed land.The objective of this paper is to present the extend of powers of the state authority in relation to reclaimed i.e. whether the state authority can alienate the reclaimed land in perpetuity or only for a lease of not exceeding 99 year.